Optical Quality and Related Factors in Ocular Hypertension: Preliminary Study - Yu-jing Wang; Yan-ning Yang; Lin-ying Huang; Bo Wang; Yu-can Han; Jiang-bo Yan (Journal of Ophthalmology)
Background. To evaluate the optical quality and related factors in patients with ocular hypertension (OHT). Methods. This was a prospective case-control study. A total of 12 eyes with OHT and 20 control eyes underwent testing with Optical Quality Analysis System II (OQAS II) to evaluate the modulation transfer function cut off frequency (MTF cutoff), the Strehl 2D ratio (SR), objective scatter index (OSI), tear-film mean OSI (TFOSI), and the OQAS values (OV100%,OV20%, and OV9%). Results. The optical quality of patients with OHT declined, with lower MTF cutoff (OHT 36.86 ± 7.11 cpd , controls 48.50 ± 4.04 cpd, t=-4.60, P<0.05), lower SR (OHT 0.22 ± 0.04, controls 0.27 ± 0.05, t=-2.72, P<0.05), lower OV100% (OHT 1.26 ± 0.25, controls 1.61 ± 0.14, t=-4.03, P<0.05), lower OV20% (OHT 1.27 ± 0.27, controls 1.72 ± 0.20, t=-4.00, P<0.05), and lower OV9% (OHT 1.30 ± 0.25, controls 1.69 ± 0.32, t=-2.28, P<0.05). There were not any statistically significant differences in OSI and TFOSI. The MTF cutoff in patients with OHT was correlated significantly with age (r=-0.59, P<0.05). Conclusions. Optical quality of patients with OHT is reduced, with lower MTF cutoff, SR, OV100%, OV20%, and OV9%. MTF cutoff is negatively related to age.